Expression and characterization of the major capsid protein derived from a GII.6 norovirus strain isolated in China. (April 2017) - Huo, Yuqi; Zheng, Lijun; Chen, Xuhui; Ge, Lili; Wang, Yumei
Abstract: The objective of this study was to express and characterize the major capsid protein (VP1) of a GII.6 Norovirus (NoV)strain isolated in China. The newly identified GII.6 NoV strain was isolated from a five-year old boy presenting acute gastroenteritis. The genome of the GII.6 strain was 7550 nucleotides in length, excluding the poly-adenylation tail. Multiple sequence alignment and phylogenetic analysis based on deduced VP1 amino acid sequences from different genotypes indicated close relationship between GII.3 and GII.6 NoVs, as demonstrated by the presence of a short sequence insertion in the P2 domain and clustering in the same subgroup. Expression of GII.6 VP1 led to assembly of virus like particles (VLPs). In vitro VLP-salivary histo-blood group antigens (HBGAs) binding assay demonstrated wide-spectrum binding activities of assembled VLPs to blood type A, B, AB and O salivary HBGAs with highest binding capacity to type A salivary HBGAs and lowest to type AB and O salivary HBGAs. In vitro VLP-salivary HBGAs binding blockade assay indicated absence of cross-blocking effects for hyperimmune sera produced against different genotypes. In conclusion, our results suggest a rational VLPs-based multivalent NoV vaccine should contain capsid proteins of a GII.6 strain. Highlights: A GII.6 norovirus strain was isolated from a 5-year-old boy presenting acute gastroenteritis and its complete genome sequence was determined. GII.6 NoV VLPs exhibited highest binding capacity against blood type A salivary HBGAs. Binding of GII.6 VLPs to salivary HBGAs could not be blocked by other genotype-specific rabbit hyperimmune sera.